Factors associated with pain induced by orthodontic separators. (1st February 2014) - Beck, V. J.; Farella, M.; Chandler, N. P.; Kieser, J. A.; Thomson, W. M.
Summary Pain resulting from the application of orthodontic forces varies markedly across individuals. The reasons of this variability are still largely unknown. To investigate factors that may be associated with orthodontic pain following the application of orthodontic separators. One hundred and seven participants were screened for pain response over 48 h following placement of orthodontic elastomeric separators. The highest (n = 10) and lowest (n = 10) pain responders were identified, and data collected on tooth pain sensitivity to electrical stimulation in conjunction with using the Pain Catastrophising Scale (PCS), Dental Anxiety Scale (DAS) and cold pressor test (CPT). There were statistically significant differences between high‐ and low‐pain responders in catastrophising score (P ≤ 0·023). For every PCS magnification score of 1 unit higher, the relative risk of being a high‐pain responder was 1·6 (P = 0·002); those scoring higher on helplessness had a lower risk of being so. DAS scores of high‐pain responders were twice as high as those of low‐pain responder (P = 0·043). During the first 2 min of CPT, the high‐pain responders experienced more pain than the low‐pain responders (P ≤ 0·029). Tooth pain thresholds did not differ between the two different pain responder groups. Pain catastrophising, dental anxiety and cold sensitivity appear to modify the pain experienced following placement of orthodontic separators. Further research is needed to determine the validity of screening questions to identify at‐risk patients prior to commencing orthodontic treatment.